Synsedimentary Deformational Structures Caused by Tectonics and Seismic Events – Examples from the Cambrian of Sweden, Permian and Cenozoic of Germany - Scholz, Herbert; Frieling, Dorothea; Aehnelt, Michaela (IntechOpen, 2011)
None